Пути решения толерантности к мочегонным лекарственным средствам при лечении отечного синдрома = Decision to tolerance diuretic drugs in the treatment of edematous syndrome - Pogorelaya, I. V. (Journal of Education, Health and Sport, 2015)
Pogorelaya I. V. Пути решения толерантности к мочегонным лекарственным средствам при лечении отечного синдрома = Decision to tolerance diuretic drugs in the treatment of edematous syndrome. Journal of Education, Health and Sport. 2015;5(11):711-719. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44262 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A711-719 http://pbn.nauka.gov.pl/works/687212 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. УДК 616.1-008.46-005.98-085.254.1/.835.3 ПУТИ РЕШЕНИЯ ТОЛЕРАНТНОСТИ К МОЧЕГОННЫМ ЛЕКАРСТВЕННЫМ СРЕДСТВАМ ПРИ ЛЕЧЕНИИ ОТЕЧНОГО СИНДРОМА DECISION TO TOLERANCE DIURETIC DRUGS IN THE TREATMENT OF EDEMATOUS SYNDROME И. В. Погорелая I. V. Pogorelaya Одесский национальный медицинский университет, г. Одесса, Украина Odessa National Medical University, Odessa, Ukraine Summary Objective: determination of effective treatment regimens for patients with heart failure NYHA III-IV and resistant edema (RE). Enrollment: 48 patients, were randomized to 2 groups. Treatment in group 1: euphilline 2 % 5 ml in sodium chloride (0.9 %) 100 ml infusion followed by furosemide i/v bolus 1 % -4.0 ml plus spironolactone 100–200 mg (BID). Treatment in group 2: furosemide 1 % 4 ml plus euphilline 2 % 5 ml (carrier 100 ml of sodium chloride 0.9 %) infusion, duration 2.5–3 hours each second day and spironolactone using the scheme adopted in group 1. Results. Group 1: insignificant improvement of edema status in 20 patients, no response in 4 patients. Group 2: significant improvement of edema status in 19 patients and complete resolve of edemas in 5 patients. Conclusions. The results of the study demonstrate the efficacy of the treatment scheme consisting of furosemidel plus euphilline infusion, duration 2.5–3 hours each second day and spironolactone. This kind of treatment provides the better results in patients with heart failure NYHA III-IV and RE. Key words: resistant edema, furosemide, euphilline, spironolactone. Резюме Целью работы - определить наиболее эффективную, экономически доступную и малоинвазивную схему лечения больных с СН II Б – III ст. III – IV ФК с рефрактерными отеками. Пролечено 48 больных. Больные рандомизированы поровну на 2 группы. В I группе больные получали фуросемид 1 % 4 мл в/в болюсно после в/в капельного введения эуфиллина 2 % 5 мл, разведенного в 100 мл 0,9 % раствора NaCl; спиронолактон 100-200 мг. Во II группе больные получали в течение 2,5-3 часов в в капельно фуросемид 1 % 4 мл с эуфиллином 2 % 5 мл, разведенные в 100 мл 0,9 % раствора NaCl через день, в сочетании с спиронолактоном по той же схеме, что и в I группе. В результате лечения у 20 больных (83,3 %) I группы наблюдалось незначительное уменьшение отеков и отсутствие эффекта от терапии у 4 больных (16,7 %). Во II группе наблюдалось значительное уменьшение отеков у 19 больных (79,2 %) и постепенное исчезновение их у 5 больных (20,8 %). Таким образом, проведенное исследование показало наиболее эффективную схему лечения (в/в капельная инфузия в течение 2,5-3 часов фуросемида с эуфиллином, в сочетании с пероральным приемом спиронолактона), что дает лучшие результаты лечения больных с СН II Б – III ст. III – IV ФК с рефрактерными отеками и является при этом малоинвазивной и экономически доступной. Ключевые слова: рефрактерные отеки, фуросемид, эуфиллин, спиронолактон.